European guidelines for quality assurance in colorectal cancer screening and diagnosis. First Edition – Organisation - Malila, N.; Senore, C.; Armaroli, P. (Endoscopy, 2012)
Multidisciplinary, evidence-based guidelines for quality assurance in colorectal cancer screening and diagnosis have been developed by experts in a project coordinated by the International Agency for Research on Cancer. The full guideline document covers the entire process of population-based screening. It consists of 10 chapters and over 250 recommendations, graded according to the strength of the recommendation and the supporting evidence. The 450-page guidelines and the extensive evidence base have been published by the European Commission. The chapter on organisation includes 29 graded recommendations. The content of the chapter is presented here to promote international discussion and collaboration by making the principles and standards recommended in the new EU Guidelines known to a wider professional and scientific community. Following these recommendations has the potential to enhance the control of colorectal cancer through improvement in the quality and effectiveness of the screening process, including multi-disciplinary diagnosis and management of the disease.
Keywords: mass screening; colorectal neoplasms; organisation; implementation; multidisciplinary evidence-based guidelines; population-based programmes